Chinese popular religion in text and acts - Chao, Shin-yi (Religion and society in Asia, 2023)
This volume explores practices and experiences in Chinese popular religion. The research adds new materials and new approaches to well-known worships such as the cults of doomsday, underworld, and Lord Guan on the one hand, and draws attention to under-the-radar deities and holy figures hiding in the mountainous countryside or among the urban crowd. While this book centers on Chinese popular religion, it will be of use to non-China scholars in folklore, religious art, and ritual studies as well as China scholars in popular culture from late-medieval to contemporary times